Recuperação de vigas de madeira deteriorada com chapa de aço parafusada - Jardim, Pedro Ignácio Lima Gadêlha (2022)
Wood is a material widely used in construction since ancient times, commonly found in historical buildings all over the planet. As wood is a biodegradable material, the constructions that use it as a structural typology, without the knowledge of the current techniques to safeguard the durability of this element, need more care regarding its protection. As a special case, historical heritage buildings have several restrictions on exchanging their elements to preserve the aesthetics and original meaning of their environments. Thus, the solution for the recovery of these degraded structures must be designed to keep as much of the original material as possible and to increase the number of elements capable of ensuring structural capacity in relation to the normative limits of rupture and service. There are several technologies for recovering and strengthening timber structures. Two usual alternatives are: the use of bolted steel plates and the use of composite materials such as fiber-reinforced polymers (FRP) bonded with epoxy adhesive. A gap was observed in the literature regarding the study of strengthening in timber beams with cross-section loss, commonly found in attacks by biotic or abiotic agents. The objective of this study was to analyze the ability to recover the flexural stiffness of steel plate bolted to hardwood beams with different cross-section losses, with a particular interest in the effect caused by different bolt arrangements in the ability to transmit the efforts from the beam to the strengthening, as well as the use of carbon fiber-reinforced polymer composites (CFRP), considering the perfect adherence and, with that, perfect transmission of the efforts between the strengthening and the beam. It was possible to observe that, despite presenting lower efficiency than the CFRP blanket, the bolted steel plate was able to return the initial stiffness in some models and the bolts specification has relevance in obtaining the results. The use of mechanical fasteners was more efficient in beams of lower strength classes, presenting a less significant difference compared to the CFRP blanket strengthening models. The region where the wood defect also occurs extensively influences the recovery capacity and the choice of adequate strengthening.